Simultaneous Determination of Hydroquinone and Catechol by Differential Alternative Pulses Voltammetry. Issue 9 (2nd May 2018) - Ayala, Alan; Stoytcheva, Margarita; Zlatev, Roumen; Velkova, Zdravka; Gochev, Velizar; Valdez, Benjamin; Montero, Gisela
Abstract: The second order voltammetric technique of high resolution, Differential Alternative Pulses Voltammetry (DAPV), was applied for the simultaneous determination of hydroquinone (HQ) and catechol (CC) on bare spectroscopic graphite electrode. Well resolved anodic and cathodic peaks situated on both sides of the zero line were obtained, while the differential pulse voltammograms were overlapped. The linear concentration range for HQ and CC quantification by DAPV was extended up to 20 μmol L −1 for both the isomers. The sensitivity of the determination was found to be 6.00 μA L μmol −1 and 3.61 μA L μmol −1, while the limit of detection reached was 0.2 μmol L −1 and 0.5 μmol L −1 for HQ and CC, respectively. No interference was observed from the commonly coexisting organic species such as resorcinol, phenol and p‐benzoquinone. The great resolution power of DAPV permitted obtaining excellent results without any electrode modification and any mathematical data processing. Abstract :